Improving Friends Matching in Social Networks Using Graph Coloring - Murad, Omayya; Sleit, Azzam; Sharaiah, Ahmad (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Recently, most of people have their own profiles in different social networks. Usually, their profiles have some brief description about their personnel picture, family members, home town, career, date of birth etc. which indicate other people know some general information about others. In social networks, usually friends recommendation is done by finding the most mutual friends and suggest them to be friends. In this paper, we will introduce an algorithm, with a linear time complexity, that helps people to get not only good friends but alsoÂ have same characteristics.Â